Re‐Dichalcogenides: Resolving Conflicts of Their Structure–Property Relationship. Issue 1 (21st October 2022) - Hasan, Md. Nur; Sorgenfrei, Felix; Pan, Nivedita; Phuyal, Dibya; Abdel‐Hafiez, Mahmoud; Pal, Samir Kumar; Delin, Anna; Thunström, Patrik; Sarma, D. D.; Eriksson, Olle; Karmakar, Debjani
Abstract: ReX2 (X = S, Se) remains a copious source of controversies and unanswered questions due to its widely contrasting experimental and theoretical results. With the help of comparative first‐principles electronic structure and phonon calculations, the correct structures for both systems are established, which minimize the apparent divergence of different experimental results. It is demonstrated that ReS2 and ReSe2 are neither iso‐structural nor iso‐electronic. The contributions of the in‐plane and out‐of‐plane orbitals at the band‐edges of the bulk and monolayers are coordinated with their anisotropic optical response. Under moderately high pressure, both of these systems are observed to undergo a semiconductor to metal transition. With the help of a combined full‐potential density functional theory and multiplet ligand field theory (DFT+MLFT) approach, the X‐ray spectral properties of these two systems are analyzed in the light of their intricate differences of optimized structures and electronic correlations. Abstract : With the help of the first‐principles electronic structure and phonon calculations, the correct structures of ReX2 (X = S, Se) are determined, which are capable of minimizing the conflicts among the theoretical and experimental results available in literature. The high‐pressure behavior and X‐ray spectral properties for these structures are predicted.